Electrochemical stability of C60 thin film supported on a Au(111) electrode at a pyrrolidinium-based ionic liquid interface. (20th August 2016) - Ueda, Hiroyuki; Nishiyama, Katsuhiko; Yoshimoto, Soichiro
Graphical abstract: Highlights: CV of C60 thin film on Au(111) electrode in [C4 mpyrr][Tf2 N] is reported. Higher scan rate facilitates insertion/expulsion of [C4 mpyrr] + in the thin film. Dissolution of the C60 film is caused by cation insertion. Higher temperatures make it difficult to detect individual redox peaks. The observed trends are related to film structure change from ion insertion. Abstract: Electrochemical stability of a fullerene (C60 ) thin film supported on Au(111) was investigated in an ionic liquid electrolyte, 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)amide ([C4 mpyrr][Tf2 N]). The prepared thin film of C60 was characterized by atomic force microscopy and scanning tunneling microscopy, which revealed homogeneous epitaxial growth with approximately 40 layers. The six successive redox states of C60 were clearly observed at room temperature by cyclic voltammetry (CV) at scan rates faster than 100 mV s −1, whereas they were hardly seen at the scan rate of 2 mV s −1 . Elevated temperature in [C4 mpyrr][Tf2 N] led to a significant decrease in the redox currents for each redox state of C60 n − ( n = 1–6) in the CV profile with increased scan cycles. The obtained result indicates that the dissolution of the C60 film is caused by cation insertion and accelerated by the generation of multiple redox states of C60 n − during the continuous scans. The redox states of C60 in [C4 mpyrr][Tf2 N] can be clearly controlled by the scan rate and temperature. The diffusion coefficient, heterogeneous rate constant, and activation energy ( D, Ea, k, and k °, respectively) of the C60 − /C60 redox couple were evaluated by CV simulation.